Increase of hippocampal glutamate after electroconvulsive treatment: a quantitative proton MR spectroscopy study at 9.4 T in an animal model of depression - Biedermann, Sarah Violetta; Zheng, Lei; Vollmayr, Barbara; Gass, Peter; Ende, Gabriele; Sartorius, Alexander (The world journal of biological psychiatry, 2012)
Objectives. Recent evidence suggests that alterations in hippocampal glutamate and gamma-aminobutyric acid (GABA) are associated with the pathomechanism of depression and treatment effects of electroconvulsive therapy (ECT). Thus, proton magnetic resonance spectroscopy (H-1 MRS) at a 9.4 T animal system seems a promising tool to study underlying mechanisms since it allows for an accurate quantification of metabolites with distinction of glutamate, GABA and glutamine, as well as separation of taurine from choline. Methods. A well-validated animal model of treatment resistant depression (congenital learned helpless rats = cLH) was investigated by hippocampal in vivo H-1 MRS with and without a 1-week course of electroconvulsive shocks (ECS), an animal model of ECT, and compared to wild type (WT) animals, while saline and clomipramine injections served as additional controls. Results. Untreated cLH rats showed significantly lower glucose and higher taurine concentrations compared to WT animals. Besides alterations on these metabolites, ECS increased glutamate in WT and cLH and choline in cLH rats. Moreover, correlations between glutamate and GABA concentrations with learned helpless behaviour were revealed. Conclusions. These findings support the idea of disordered hippocampal metabolism in an animal model of treatment resistant depression and suggest an early impact of ECS on MR-detectable hippocampal metabolites.
Gesehen am 18.06.2018
Published online: 18 Jul 2011